ASAS REBUS SIC STANTIBUS DALAM KASUS KREDIT MACET TERHADAP ADANYA KEBIJAKAN PEMBATASAN SOSIAL BERSKALA BESAR DI INDONESIA - Kurniadi Prasetyo (Fakultas Hukum, Universitas Muhammadiyah Pontianak, 2020)
The corona virus outbreak caused the government to issue a Large-Scale Social Restriction policy (PSBB). The policy affects changes in circumstances including changes in economic conditions due to the number of bad credit problems. The application of the sic stanntibus stew principle should be the solution of the problem. This study analyzes the regulation of the principle of sic stantibus stew in Indonesia and the application of the sic stantibus stew principle in the case of bad credit to the PSBB policy in Indonesia. The method used in this research is normative legal research. The results showed that the Rebus sic stantibus principle can be applied by renegotiating the problem of bad credit based on the principle of freedom of contract. Article 1338 paragraph (2) of the Civil Code is a legal basis for applying the sic stantibus stew principle.